2017
DOI: 10.1111/jvim.14725
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of Oral Sugar Test Results, Glucagon‐Like Peptide‐1 Measurements, and Serum High‐Molecular‐Weight Adiponectin Concentrations in Horses

Abstract: BackgroundRepeatability of the oral sugar test (OST) has not been evaluated.ObjectivesWe hypothesized that OST glucose, insulin, active (aGLP‐1) and total (tGLP‐1) glucagon‐like peptide 1, and high‐molecular‐weight (HMW) adiponectin results would be repeatable.AnimalsFifty‐three horses from a Tennessee research facility (n = 23) and private practice in Missouri (n = 30), including animals with medical histories of equine metabolic syndrome.MethodsTwo OSTs were performed 7–14 days apart and plasma glucose and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 38 publications
7
47
1
Order By: Relevance
“…A previous study found within subject agreement for a single sample to be moderate to fair, with the same animal having varying response at the same time point . A study using larger numbers of animals (n = 53) found the agreement to be good at 60 and 75 min . AUC i was more repeatable in the present study than a single time point.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…A previous study found within subject agreement for a single sample to be moderate to fair, with the same animal having varying response at the same time point . A study using larger numbers of animals (n = 53) found the agreement to be good at 60 and 75 min . AUC i was more repeatable in the present study than a single time point.…”
Section: Discussionsupporting
confidence: 57%
“…Although testing was undertaken up to 120 min in this current study, no further blood samples were taken beyond that point; therefore, it is not possible to state whether a difference would have been seen at 180 min. However, a more recently published study with larger numbers, found no significant difference in glucose response between insulin dysregulated and normal animals at time 0–75 min on two occasions. It is surprising that the dose relationship in this study was not incremental in that 0.45 mL/kg BW dose did not lead to a significantly higher glucose response than the 0.3 mL/kg BW dose.…”
Section: Discussionmentioning
confidence: 78%
“…One study [2] reported a high coefficient of variation (CV) (45%) for the insulin area under the curve (AUC Insulin ). Another reported a lower median CV (15.3%) but a wide range (0.3-78.5%) of individual horse CVs [9].…”
Section: Introductionmentioning
confidence: 95%
“…For example, based on the CR for Insulin 60–120 , a horse needs to have a change of at least 14.5 μIU/mL at re‐assessment in order to have 95% confidence that the change has clinical relevance. In comparison, horses with normal insulin regulation are reported to have CR of 38.7 μIU/mL for single samples of plasma insulin taken at 60 min of an OST . These CRs are thus absolute index values for repeatability with the same unit but they are not directly comparable with each other.…”
Section: Discussionmentioning
confidence: 97%